Prevalence of traumatic brain injury and attention deficit hyperactivity disorder in secure settings: a pilot study - Kelsey, David (The journal of forensic psychiatry & psychology, 2024)
Traumatic brain injury (TBI) is associated with higher rates of violent crime, poorer educational outcome, and more frequent convictions. Attention deficit hyperactivity disorder (ADHD) has been associated with both an increased risk of interpersonal violence and previous TBI. We estimated the prevalence of TBI and ADHD in inpatients admitted to forensic psychiatric inpatient settings and a psychiatric intensive care unit using three validated screening questionnaires supplemented with a review of electronic health records. Sixty adult male participants were recruited. Over two-thirds screened positive for TBI. Over one-third of these reported experiencing more than one head injury. Over two-thirds screened positive on one ADHD screening questionnaire (ASRS) which was positively associated with previous TBI. A little under one-third screened positive on another ADHD screening questionnaire (B-BAARS). This is the first study attempting to estimate the prevalence of ADHD and TBI in forensic inpatient settings. There remains a lack of consensus on the gold standard screening tool for TBI in populations with psychotic disorders. Further research is needed to identify accurate and reliable detection methods for estimating the prevalence of TBI and ADHD in this highly resource-intensive, and under-studied, clinical population.